Post Post Infidelity Stress Disorder and Violence among Intimate Partners in Nigeria - Edafe Ulo; Annmarie Nkem Okoli (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Infidelity represents a severe relational stressor that may trigger Post-Infidelity Stress Disorder (PISD) and increase the risk of intimate partner violence (IPV), yet empirical evidence within the Nigerian context remains limited. Objective: This study examined the predictive relationship between PISD and IPV and assessed the moderating role of coping strategies, while exploring differences across gender and age groups. Method: A quantitative cross-sectional design was employed. Data were collected from intimate partners using standardized instruments measuring post-infidelity stress, coping strategies, and IPV. Multiple regression and moderation analyses were conducted to determine predictive effects and interaction patterns. Result: PISD significantly predicted IPV, accounting for 38% of the variance in violent behaviour. Individuals with elevated PISD were 3.14 times more likely to engage in IPV. Females reported higher PISD levels, whereas younger adults demonstrated greater vulnerability to IPV and maladaptive coping. Adaptive coping strategies significantly reduced the strength of the PISD–IPV association. Conclusion: Post-infidelity stress constitutes a substantial psychological risk factor for intimate partner violence. The interaction between stress responses and coping styles plays a critical role in shaping behavioural outcomes within intimate relationships. Contribution: The findings provide empirical evidence to inform culturally responsive counseling and violence-prevention interventions in Nigeria.